Diet and diet‐associated bacteria shape early microbiome development in Yellowtail Kingfish (Seriola lalandi). Issue 2 (1st December 2018) - Wilkes Walburn, Jackson; Wemheuer, Bernd; Thomas, Torsten; Copeland, Elizabeth; O'Connor, Wayne; Booth, Mark; Fielder, Stewart; Egan, Suhelen
Summary: The supply of quality juveniles via land‐based larviculture represents a major bottleneck to the growing finfish aquaculture industry. As the microbiome plays a key role in animal health, this study aimed to assess the microbial community associated with early larval development of commercially raised Yellowtail Kingfish ( Seriola lalandi ). We used qPCR and 16S rRNA gene amplicon sequencing to monitor changes in the microbiome associated with the development of S. lalandi from larvae to juveniles. We observed an increase in the bacterial load during larval development, which consisted of a small but abundant core microbiota including taxa belonging to the families Rhodobacteraceae, Lactobacillaceae and Vibrionaceae . The greatest change in the microbiome occurred as larvae moved from a diet of live feeds to formulated pellets, characterized by a transition from Proteobacteria to Firmicutes as the dominant phylum. A prediction of bacterial gene functions found lipid metabolism and secondary metabolite production were abundant in the early larval stages, with carbohydrate and thiamine metabolism functions increasing in abundance as the larvae age and are fed formulated diets. Together, these results suggest that diet is a major contributor to the early microbiome development of commercially raised S. lalandi . Abstract : This study describes the dynamic nature of the early microbiome of commercially raised S. lalandi . The results show that while a core set of taxa can be found across all larval stages the microbiome is strongly influenced by the bacteria associated with the feed. These findings speak to the possibility of using feed‐based inoculation of the gut microbiome to improve fish production and meet the increasing demand on aquaculture.